Individualised Homeopathic Treatment of Nausea and Vomiting in the First Trimester and of COVID-19 in the Third Trimester of Pregnancy—A Case Report - Glas, Katarina Lucija (Homeopathy, 2022)
Introduction/Background Nausea and vomiting in pregnancy are common physiological disturbances, causing physical, social and psychological symptoms in the affected women. Though it is difficult to draw absolute conclusions on whether or not pregnant women are at high risk of acquiring severe consequences from corona-virus disease 2019 (COVID-19), clinical experience has shown them to be potentially vulnerable to other coronaviruses. Lack of specific conventional therapy for these conditions called for a complementary and individualised homeopathy approach in the presented case.Methods The homeopathic medical management of early symptoms of nausea and vomiting in pregnancy (NVP) and the beginning of COVID-19 symptoms shortly before a scheduled Caesarean section is described. No ongoing specific treatments were discontinued. The connection between intervention with individualised homeopathy and clinical improvement was assessed by two independent reviewers using the MOdified NARanjo Criteria for Homeopathy (MONARCH) inventory.Results There was improvement of NVP symptoms in early pregnancy and in later-onset COVID-19 symptoms following an individually prescribed unipotent homeopathic medicine, Sepia officinalis, after tele-consultation during lockdown. The agreed MONARCH score was +8 points, suggesting that homeopathy contributed to clinical improvement.Conclusion Individualised homeopathy may be a helpful complementary medical approach for managing symptoms associated with NVP and COVID-19 during pregnancy.
Keywords: homeopathy; pregnancy; nausea and vomiting; morning sickness; COVID-19; individualised homeopathy; tele-consultation